MOvalues: A Value-Oriented Method for Evaluating Online Social Networks - Canal, Maíra Codo; Pereira, Roberto (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2020: Anais do XIX Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2020)
The Human-Computer Interaction (HCI) community has reported a lack of well-established evaluation methods based on human values. Neglecting values in computing systems can result in a system that does not make sense to users, that does not serve stakeholders, and that can trigger undesirable impacts, difficult to predict and reverse, in the context in which it is used. This situation is even more critical for widely used systems, such as Online Social Networks (OSN). This paper presents a value-oriented method for the evaluation of OSN. The method is based on Organizational Semiotics and inspired by the heuristic evaluation. The method was evaluated by representatives from its target audience and results were positive about its ease and usefulness of use, showing potential to contribute to discussions and practices on human values in HCI.